Technological Mineralogical Characteristics and Mineral Processing Test of Donganshan Iron Ore - Shuyong LIU; Guang YANG; Libin YUAN; Shushuang CONG; Jiangning ZHANG; Zhanliang NIU (Kuangchan zonghe liyong, 2024)
This is an article in the field of mineral processing engineering. In order to accurately grasp the influence of various types of ores on field production, the process mineralogy of various types of ores was systematically and deeply studied by means of chemical analysis and automatic mineral analysis system (AMICS). Based on the process mineralogy, the ore blending scheme was drawn up, and the whole process test was carried out according to the optimal ore blending ratio. The results show that all kinds of ores are lean iron ores with high silicon, low iron and low sulfur and phosphorus. The embedding characteristics of various types of ores are complex, which has a certain influence on the grindability of ores and monomer dissociation. According to the washability test results of various types of ores in the mining area, the comprehensive ore blending ratio is determined as follows: (magnetic ore∶ sub-iron ore∶ eastern red ore∶mixed ore∶ chlorite ore∶ iron carbonate ore) =(25∶25∶25∶10∶10∶5). Through the closed-circuit process of weak magnetic field-strong magnetic field-mixed magnetic fine anion reverse flotation, the comprehensive ore blending obtained good indexes of comprehensive concentrate grade of 66.06%, yield of 34.60%, comprehensive tailings grade of 15.20% and yield of 65.40%.